223. Dosimetric characterization of the iBEAM evo carbon fiber couchtop for Monaco radiotherapy treatment planning. (December 2018) - Zefiro, D.; Piergentili, M.; Bampi, R.; Foppiano, F.
Abstract : Purpose: The dosimetric impact from devices external to the patient is not negligible and it is a complex combination of increased skin dose, reduced tumor dose, and altered dose distribution[1] . Beam attenuation resulting from the interaction with a carbon fiber couchtop (CFC) may be accounted for in treatment delivery incorporating the couchtop in the treatment planning system (TPS). The purpose of this study is to tweak the electron densities of the iBEAM evo CFC model implemented in the TPS Elekta Monaco. Methods: A cylindrical plastic phantom with a diameter of 32 cm was used and a ion chamber was inserted into the central hole. It was placed on the radiotherapy couch and it was irradiated with a constant dose rate 6MV photon arc beam. The dose was measured as a function of gantry angle. This setup was replicated in Monaco and dose was calculated at gantry angles ranging from 0° to 360° in 10° increment. The TPS supplied couch model was adapted by changing the electron density of its components in order to match the measured and calculated relative doses. Results: The optimized relative electron densities for CFC components were 0.065 for foam core and 0.7 for carbon fiber. The average beam attenuation was about 3–4%. Conclusions: A correct matching of the CFC model implemented in the TPS yield to accurate dose calculation, in particular for 360° volume arc therapy and stereotactic treatments.